Determination of cell shape in Staphylococcus aureus - Tavares, Andreia Filipa Campos (2019)
"Cell size and morphology are two extremely important characteristics in the adaptation of bacteria to the external environment and are often associated to bacterial survival and growth. In Staphylococcus aureus, a common colonizer of human skin and mucus membranes, the small spherical shape of cells may be an advantage during colonization, helping this pathogen to evade host immune system. The fact that cell shape is maintained over consecutive generations evidences the existence of tightly regulated underlying mechanisms. Bacterial shape is maintained by the existence of an external cell wall mainly composed of peptidoglycan (PGN), a mesh-like molecule made by glycan chains cross-linked by short peptide bridges. Localization of PGN synthesis is dependent on the action of cytoskeletal proteins, which direct the activity of proteins involved in this synthesis, including Penicillin-Binding Proteins (PBPs) and proteins from the shape, elongation, division and sporulation (SEDS) family, to specific regions of the cells. T(...)"